Integrated Communicative-Based English Instructional Materials for Non-English Department Students - Ribahan; Muhsinin; Hery Rahmat (Prodi Tadris Bahasa Inggris, 2024)
This study aimed to develop integrated communicative-based English instructional materials for non-English department students at Universitas Islam Negeri (UIN) Mataram, employing the ADDIE instructional design model, which includes analysis, design, development, implementation, and evaluation. Data were collected through questionnaires, interviews, and tests. The questionnaires and interviews gathered information on student needs, validity, and practicability of the instructional materials, while tests assessed the effectiveness of the instructional materials in the classroom. Quantitative and qualitative analyses revealed that the existing English instructional materials had not been developed properly, confirming the need to create new English instructional materials aligned with the principles of an integrated communicative approach. The findings also indicated that experts, students, and lecturers found the newly developed instructional materials valid, practical, and effective in enhancing student achievement in learning English.